Shelley's Frankenstein - Allen, Graham, 1963- (Continuum reader's guides., 2008)
"Mary Shelley's classic gothic novel, Frankenstein, is one of the most widely studied novels in English Literature. Due to its key position in the canon and its wide cultural influence, the novel has been the subject of many interpretations, which require some guidance to navigate. This book offers an authoritative, up-to-date guide for students, introducing its context, language, themes, criticism and afterlife, leading them to a more sophisticated understanding of the text." "Graham Allen places Frankenstein in its historical, intellectual and cultural contexts, offering analyses of its themes, style and structure, providing exemplary close readings, and presenting an up-to-date account of its critical reception. It also includes an introduction to its substantial history as an adapted text on stage and screen and its wider influence in film and popular culture. It includes points for discussion, suggestions for further study and an annotated guide to relevant reading."--Jacket